Prevention of human trafficking: a study on Malaysia’s anti-trafficking in persons and anti-smuggling of Migrants Act 2007 - Ab Hamid, Zuraini (International Organization Center of Academic Research (OCERINT), 2015)
United Nations Universal Declaration of Human Rights 1948 and Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children are the two core international conventions that have found the inclusion of human trafficking issue into international relations. Both of the international written documents have provided excellent guidelines to their state members in combating the heinous crime. In that context, the later has outlined “3P” paradigm to combat human trafficking where the major concern is given to prevent the crime, protect the victims and prosecute the perpetrators. Among the three, the prevention of human trafficking becomes the key component of the paradigm which practically is conducted through various public awareness campaigns, strengthening corporation between government and non-governmental organizations and implementation of laws. The campaign will acknowledge the issue, educate public to identify the vulnerable victims for trafficking and warn the migrant about the risk of their migration to the foreign countries. Then, a strong corporation between the parties will enhance the success. However, nobody can deny the power of laws, which can restrain an individual from committing any offence. Therefore, this paper provides legal analyses to determine whether the Malaysia‟s legal response through its AntiTrafficking in Persons and Anti-Smuggling of Migrants Act 2007 is in compliance with the international paradigm. This paper discloses that the Act has shown its capability in preventing the crime. However, an extensive effort could be taken in order to strengthen the paradigm of prevention in the Act where a greater priority should be given to the protection of the victim and enforcement of the Act itself.